2018
DOI: 10.3389/fmolb.2018.00106
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serine Racemase-Dependent Modulation of NMDA Receptor: Impact on Physiological and Pathological Brain Aging

Abstract: The N-methyl-D-Aspartate glutamate receptors (NMDARs) are pivotal for the functional and morphological plasticity that are required in neuronal networks for efficient brain activities and notably for cognitive-related abilities. Because NMDARs are heterogeneous in subunit composition and associated with multiple functional regulatory sites, their efficacy is under the tonic influence of numerous allosteric modulations, whose dysfunction generally represents the first step generating pathological states. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 191 publications
0
13
0
7
Order By: Relevance
“…Of note, D-serine is also regulated by many other mechanisms such as serine racemase that synthesizes D-serine from L-serine 45 . Serine racemase has also been thought to play a role in the aging process 46 . Other modulatory mechanisms should be also considered when the relationship between pLG72 and D-serine and L-serine is explored.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, D-serine is also regulated by many other mechanisms such as serine racemase that synthesizes D-serine from L-serine 45 . Serine racemase has also been thought to play a role in the aging process 46 . Other modulatory mechanisms should be also considered when the relationship between pLG72 and D-serine and L-serine is explored.…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation indicates that Asc-1 activity remained unchanged in the aging hippocampus [48]. Considering that mechanisms underlying the degradation and release of D-serine are not altered in physiological aging, alterations in synthesis therefore appears as the critical mechanism underlying the age-related decrease of the NMDAr co-agonist availability [42,43].…”
Section: D-serine In Physiological Agingmentioning
confidence: 99%
“…Thereafter, it was observed that a supplementation with the amino acid was able to prevent age-induced deregulation of NMDAr activation and to restore hippocampal synaptic plasticity [34][35][36][37]. Beyond the decrease in NMDAr density (or its subunits) initially evoked [38][39][40][41], these promising results rather argue for a pivotal role of D-serine in functional mechanisms underlying cognitive aging [42,43].…”
Section: D-serine In Physiological Agingmentioning
confidence: 99%
“…Here, we provide evidence that the hypofunction of NMDARs resembles many manifestations observed during aging such as disturbed glomerular filtration, alterations in the skin turnover and bone remodeling, suggesting that NMDARs hypofunction could be associated with deterioration due to aging. We propose that a decrease in D-serine could account for this hypofunction because (1) NMDAR hypofunction in the brain associated with aging is related with a decrease in the synthesis of D-serine and not glycine ( Mothet et al, 2006 ; Billard, 2018 ); (2) There is an increase of DAAO in the plasma associated with age ( Lin et al, 2017 ); (3) NMDAR expressed in glomerular podocytes are insensitive to glycine ( Anderson et al, 2011 ); (4) NMDAR activation induces vasodilation through the increase in NO production in a D-serine concentration-dependent manner ( LeMaistre et al, 2012 ; Lu et al, 2019 ); (5) D-serine administration induces a dose-dependent and NMDAR dependent relaxation of cavernosal tissue pre-contracted with phenylephrine ( Ghasemi et al, 2010 ); and (6) SR and NMDAR are localized in the keratinocytes of the skin ( Inoue et al, 2014 ).…”
Section: Role Of D-serine In the Hypofunction Of Nmdars In The Peripherymentioning
confidence: 99%